8
$\begingroup$

For any postive integer number $n\ge 2$, show that

$$\dfrac{3}{4}\le\left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}<1$$

My try:let $\dfrac{1}{n}=x$, then $$\left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}=x^{\frac{x}{1-x}}+x^{\frac{1}{1-x}}(0<x<1)$$ maybe use Young's inequality.

But I can't,and I think this problem have more nice methods,Thank you

$\endgroup$
0

2 Answers 2

4
$\begingroup$

Note that, for every $n\geqslant2$, $$ \left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}=\frac{n+1}{n^{n/(n-1)}}=\mathrm e^{u(n)}, $$ where, for every $x\gt1$, $$ u(x)=\log(x+1)-\frac{x}{x-1}\log x. $$ Thus, $$ u'(x)=\frac{v(x)}{(x-1)^2},\qquad v(x)=\log(x)-2\frac{x-1}{x+1}. $$ which yields $$ v'(x)=\frac1x-\frac4{(x+1)^2}=\frac{(x-1)^2}{x(x+1)^2}. $$ Now, $v(1)=0$ and $v$ is increasing hence $v\gt0$ and $u$ is increasing on $(1,+\infty)$, in particular, for every $n\geqslant2$, $$ u(2)\leqslant u(n)\lt u(+\infty). $$ Note that $u(2)=\log3-2\log2$ and that $u(x)$ is also $$ u(x)=\log\left(1+\frac1x\right)-\frac{\log x}{x-1}, $$ hence $u(+\infty)=0$. Finally, for every $n\geqslant2$, $$ \frac34=\mathrm e^{u(2)}\leqslant\left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}\lt\mathrm e^{u(+\infty)}=1. $$

$\endgroup$
1
  • $\begingroup$ Thank you,It's nice.and for this right,use Bernoulli inequality:w we have $$\le 1+\dfrac{1}{n-1}(\dfrac{1}{n}-1)+\dfrac{n}{n-1}(\dfrac{1}{n}-1)=1$$ $\endgroup$
    – math110
    Oct 20, 2013 at 17:24
1
$\begingroup$

I think there is a much simpler way. Notice that $\left(\frac{1}{n}\right)^{\frac{1}{n-1}}+\left(\frac{1}{n}\right)^{\frac{n}{n-1}}$ can be expressed as: $$ a_n=\frac{n+1}{n}\left(\frac{1}{n}\right)^{\frac{1}{n-1}},$$ and we only need to prove that the sequence $\{a_n\}_{n\in\mathbb{N}}$ is increasing, since its limit is clearly $1$. $a_{n+1}\geq a_{n}$ is equivalent to: $$ n^{n^2} (n+2)^{n(n-1)} > (n+1)^{2n^2-n-1}, $$ or to: $$\frac{(n+1)^{(n+1)}}{(n+2)^n}>\left(\frac{(n+1)^2}{n(n+2)}\right)^{n^2},$$ Notice that in virtue of the Bernoulli inequality the LHS is greater that $\frac{n+2}{e}$, while the RHS is smaller than $e$, so for any $n\geq 6$ the inequality holds for sure, and we have to check only $n=2,3,4,5$, for which the difference between the LHS and the RHS is indeed positive by hand (or computer) computation.

$\endgroup$
3
  • $\begingroup$ This proves the inequality for $n$ large enough, not for every $n\geqslant2$. $\endgroup$
    – Did
    Oct 20, 2013 at 19:04
  • $\begingroup$ That's true, but one can check the other cases ($n<6$) by hand. $\endgroup$ Oct 21, 2013 at 7:41
  • $\begingroup$ Then one should add an actual proof that "the other cases" are only when $n\leqslant5$. $\endgroup$
    – Did
    Oct 21, 2013 at 8:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.